2017
DOI: 10.1038/s41467-017-01369-8
|View full text |Cite
|
Sign up to set email alerts
|

Development of corticostriatal connectivity constrains goal-directed behavior during adolescence

Abstract: When pursuing high-value goals, mature individuals typically titrate cognitive performance according to environmental demands. However, it remains unclear whether adolescents similarly integrate value-based goals to selectively enhance goal-directed behavior. We used a value-contingent cognitive control task during fMRI to assess how stakes—the value of a prospective outcome—modulate flexible goal-directed behavior and underlying neurocognitive processes. Here we demonstrate that while adults enhance performan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
78
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(85 citation statements)
references
References 81 publications
6
78
1
Order By: Relevance
“…We hypothesized that distinct potential developmental patterns might emerge in our study depending on the neurocognitive mechanisms underpinning the influence of the utility of agency on memory. One possibility was that prioritizing memory according to the utility of agency requires cognitive control processes that continue to develop with age (Davidow et al, 2018;Insel et al, 2017;Störmer et al, 2014). Past work has demonstrated that intentional prioritization of memory for information explicitly labeled as "high-value" is evident in middle childhood, but markedly improves into adulthood (Castel et al, 2011;Hanten et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We hypothesized that distinct potential developmental patterns might emerge in our study depending on the neurocognitive mechanisms underpinning the influence of the utility of agency on memory. One possibility was that prioritizing memory according to the utility of agency requires cognitive control processes that continue to develop with age (Davidow et al, 2018;Insel et al, 2017;Störmer et al, 2014). Past work has demonstrated that intentional prioritization of memory for information explicitly labeled as "high-value" is evident in middle childhood, but markedly improves into adulthood (Castel et al, 2011;Hanten et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…One possibility is that the ability to prioritize memory based on its potential future value requires cognitive control processes that continue to develop into adulthood. The ability to adaptively modulate cognitive effort based on potential reward improves through late adolescence (Castel et al, 2011;Davidow, Insel, & Somerville, 2018;Hanten et al, 2007;Insel, Kastman, Glenn, & Somerville, 2017;Störmer, Eppinger, & Li, 2014). If prioritizing the encoding of choice outcomes is an effortful goal-directed process, then the ability to preferentially allocate this cognitive resource to contexts in which agency has utility would likely continue to develop into adulthood.…”
Section: Introductionmentioning
confidence: 99%
“…The ability to use explicit value cues to proactively modulate control improves across development (Davidow, Insel, & Somerville, 2018). Relative to children, adults and older adolescents are better, for example, at selectively enhancing attention (Störmer, Eppinger, & Li, 2014) and inhibitory control (Insel, Kastman, Glenn, & Somerville, 2017) when the reward they can earn for doing so is high. If the use of learned value signals to influence encoding similarly relies on the flexible engagement of cognitive control processes, then memory prioritization may improve over development even after accounting for age-related differences in learning about environmental regularities.…”
Section: Introductionmentioning
confidence: 99%
“…Because we had specific hypotheses about the role of corticostriatal circuitry in value-guided cognitive control (Botvinick & Braver, 2015;Davidow et al, 2018a), we constrained this analysis to interrogate voxels within anatomical masks comprising the bilateral vlPFC (frontal operculum) and bilateral ventral and dorsal striatum (caudate, putamen, and nucleus accumbens). These regions were chosen based on prior work which found enhanced recruitment of these systems during incentivized control in the same 13 to 20 year old age range tested in the present study (Insel et al, 2017). This age covariate analysis identified increased activity for previously learned high gain relative to low gain NoGo cues that increased with age across adolescence in the caudate and in the frontal operculum, extending to the inferior frontal gyrus (Figure 3b, Table 3).…”
Section: Functional Activity Analysesmentioning
confidence: 84%
“…Functional MRI data were carefully evaluated for motion and signal outliers given the negative impact it can have on signal quality and GLM estimates. The following rules were imposed for exclusion of functional data as in our prior work (Insel et al, 2017;Insel & Somerville, 2018). Runs in which more than 10% of TRs were censored for motion (relative motion > 1mm) or outlier signal intensity (exceeded the grand run median by 4.5 median absolute deviations) were excluded from analysis.…”
Section: Fmri Data Processing and Quality Assessmentmentioning
confidence: 99%